Concepts for Integrated Planning of Port Capacity- Application to Rotterdam Expansion Plans - Dekker, Sander; Verhaeghe, Robert (Promet - Traffic&Transportation, 2006)
Port planning is complicated due to many factors, includingthe existence of economies of scale in port expansion andthe fact that ports operate under competition. The port plannershould provide an overview of all potential strategies to enhanceport competitivness. Choices should be made with tailoreddesign concepts within a framework comprising supply-demand planning and cost-benefit analysis. Port expansionis a strategy to enhance port competitiveness and can be characterizedas a stmctural port capacity measure. Non-structuralalternatives comprise supply and demand management measuresand aim at efficient capacity utilization. In the design ofport expansion, a certain level of traffic congestion should beaccepted. Full integration of port-commercial and public interestsby combining structural and non-structural capacity measuresis essential for planning of port capacity. Efficiency, themain guiding principle for such planning, addresses the simultaneousdetermination of 1) optimal expansion size, and 2) investmentrecovery period.